Electrification, urban life and the role of women - Carvalho de Lima Seabra, Odette (Geografares, 2020)
Technological innovations have significantly changed the society in many ways. This paper analyses the major changes caused by the development and the spread of electric energy utilization in the production of urban space, in labour, in the organization of family and households, in everyday life and in the role of women, such as the changes brought to the households as an outcome of the introduction of everyday technologies in them, as well as in the role they play, whether in the job market, in the artistic and political vanguards and in the fight for rights, as well as in their role of household management as the person responsible for maintaining the conditions of social reproduction of their families. This debate is supported by the notions of modern, modernization, modernity and utopia, while highlights the contradictions and inequalities that remain and permeate the life of the working class in the cities.